Can trainability constrain physical fitness adaptations to small-sided games and high-intensity interval training in young male basketball players? a prospective cohort study - Wei, LiXin; Zheng, YaFei (Frontiers in Physiology, 2024)
IntroductionResearch on the effects of training programs involving small-sided games (SSG) versus high-intensity interval training (HIIT) has been increasing in recent years. However, there is limited understanding of how an individual's initial physical fitness level might influence the extent of adaptations achieved through these programs. This study aimed to compare the impacts of SSG and HIIT on male soccer players, while also considering the players' athleticism, categorized into lower and higher total athleticism score (TSA).MethodsA prospective cohort study was conducted over a 6-week pre-season training period, involving 43 male soccer players from regional-level teams (average age 16.5 ± 0.7 years). Players were evaluated at the start and after the 6-week period. One team incorporated SSG as a core component of their aerobic-based training, while the other team used HIIT. Evaluations included a countermovement jump (CMJ) test, a 30-meter linear sprint test, and the 30–15 intermittent fitness test (30–15 IFT). TSA was calculated to assess each player's overall athleticism level (classifying them as fit and non-fit).ResultsResults revealed that non-fit players showed significantly greater CMJ improvements (mean difference: 3.0 cm; p < 0.005) and VIFT improvements (mean difference: 0.682 km/h; p = 0.002) in SSG compared to fit players. In the HIIT group, non-fit players also revealed greater improvements than fit players in CMJ (mean difference: 2.5 cm; p < 0.005) and peak speed in sprint (mean difference: 0.706 km/h; p = 0.002). No significant differences were found between groups regarding the observed improvements.DiscussionIn conclusion, this study suggests that the initial level of physical fitness significantly influences the magnitude of adaptations. Specifically, players with lower fitness levels appear to benefit more from training interventions. Improvements in CMJ and aerobic capacity in SSG seem to depend on players’ fitness levels, and a similar trend is observed in HIIT for CMJ and peak speed. Individualizing training programs is recommended, with a focus on providing greater or different stimuli to more well-prepared players to ensure their continued development.